Progeny Trial of Acacia catechu - Gera, Mohit; Awadhiya, Ankur; Gera, Neelu (Indian Forester, 2016)
Twenty eight Candidate Plus Trees of Acacia catechu were selected from within different locations of Jammu region based on their superior phenotypic characteristics. Their progeny, in the form of seeds were collected, and the seedlings were raised and planted in four replications in the year 1999 in Basanter Bela, Samba district of Jammu region. Following maintenance, these plants were analysed in the year 2011 for survival and growth characteristics of height, girth at breast height and crown area. It was observed that the differences in progeny characteristics observed between the families were highly significant. The growth parameters of height, girth at breast height and crown area were correlated to a high degree, but the degree of correlation with the parents was observed to be not significant. The maximum values of mean height, mean girth at breast height and mean crown area were 121.11%, 136.41% and 161.57% of the minimum values, respectively, as observed among the families. Based on the field observations three families i.e., 2, 11 and 14, on account of the maximum values of mean height, mean girth at breast height and mean crown area are recommended for future plantation purposes and further tree improvement work.